2021
DOI: 10.3390/jcm10061294
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Femoral Cartilage T2 Relaxation Time and Thickness Changes with Fast Sequential Radiographic Progression of Medial Knee Osteoarthritis—Data from the Osteoarthritis Initiative (OAI)

Abstract: This study tested for longitudinal changes in femoral cartilage T2 relaxation time and thickness in fast-progressing medial femorotibial osteoarthritis (OA). From the Osteoarthritis Initiative (OAI) database, nineteen knees fulfilled the inclusion criteria, which included medial femorotibial OA and sequential progression from Kellgren–Lawrence grade (KL) 1 to KL2 to KL3 within five years. Median T2 value and mean thickness were calculated for six condylar volumes of interest (VOIs; medial/lateral anterior, cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Considered as the essential part of OA, cartilage is the most-commonly assessed structure in quantitative MRI of OA research. 29,30,33,39 Previous studies have reported that cartilage thickness decreased in the medial load-bearing regions primarily between K-L grade 2 and K-L grade 3 radiographic stages, 29 while it increased in the posterior aspect of femoral condyles throughout the disease due to anabolic processes initiated in reaction to OA. 30 However, Reichenbach et al 33 reported that quantitative measurement of cartilage volume and thickness did not distinguish focal cartilage loss in mild OA from non-OA, which could be detected by experienced readers applying semiquantitative methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considered as the essential part of OA, cartilage is the most-commonly assessed structure in quantitative MRI of OA research. 29,30,33,39 Previous studies have reported that cartilage thickness decreased in the medial load-bearing regions primarily between K-L grade 2 and K-L grade 3 radiographic stages, 29 while it increased in the posterior aspect of femoral condyles throughout the disease due to anabolic processes initiated in reaction to OA. 30 However, Reichenbach et al 33 reported that quantitative measurement of cartilage volume and thickness did not distinguish focal cartilage loss in mild OA from non-OA, which could be detected by experienced readers applying semiquantitative methods.…”
Section: Discussionmentioning
confidence: 99%
“…Cartilage volume and thickness assessed by MRI have been regarded as important quantitative markers of knee osteoarthritic status. 29 , 30 , 33 , 39 The DESS DICOM data were analyzed in Mimics (Materialize Interactive Medical Image Control System; 26.0) software. Slice by slice, the profiles of the patellar, femoral and tibial cartilage were outlined manually.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these studies, 41 articles met inclusion criteria with clear definitions of radiographic KOA progression described. There were 28 studies that analyzed various risk factors for progression, with specific definitions of radiographic KOA progression as the outcome variables (Table 1) [4, 5, 8, 9, 12–17, 21, 25, 26, 28, 31, 32, 34, 35, 38, 39, 41, 43, 46–51]. The 13 other studies out of the 41 total created or validated prediction models, tools, or risk calculators for radiographic KOA progression (Table 2) [1, 7, 10, 11, 18, 20, 22–24, 29, 33, 36, 40].…”
Section: Resultsmentioning
confidence: 99%
“…Baseline MRI compositional markers may not provide better discrimination between knees with OA progression and those without signi cant progression than simple radiographic measures [20,21]. Edd et al investigated longitudinal change in femoral cartilage T2 value and thickness in progressive OA and found that T2 values increased in the early stage and cartilage thickness decreased mainly in the later stage [22]. These ndings support the ability of the cartilage imaging biomarker to predict OA severity and progression dependent on the disease stage.…”
Section: Discussionmentioning
confidence: 99%